Analisa Penegakan Hukum dan Pengawasan Keimigrasian pada Kasus Masuknya Warga Negara China Ditengah Masa Pandemi Covid-19 - Muhammad Fachryza; Muhammad Faiz Febriandana; Yofan Gusti Pratama (Universitas Batanghari Jambi, 2021)
Immigration officers while implementing their functions as well as state gatekeepers have a very important role in the situation of the spread of the covid-19 virus in the world. Immigration has four functions of immigration, namely service, security, law enforcement, and facilitator for state development. In a scientific paper with the theme of analysis of law enforcement and immigration control with case studies of the entry of Chinese nationals in the midst of the COVID-19 pandemic. where law enforcement and supervision of people during the current pandemic is very risky because it will have a number of differences where in this difficult time or in the New Normal adaptation period in Indonesia, immigration can actually develop and adjust in law enforcement both Indonesian citizens and foreigners. The government itself, in collaboration with the Directorate General of Immigration, provides new regulations and policies relating to the implementation of the main duties and functions of immigration, including including law. This scientific work aims to provide an explanation regarding immigration law enforcement and the supervision of foreigners carried out during the Covid-19 pandemic, and is also based on Indonesian government policies, especially immigration in preventing the spread of Covid-19.